Proposals to Sell, Annex or Evacuate Iceland, 1518–1868 - Hannes Hólmsteinn Gissurarson 1953- (2015)
Iceland, a remote country with a harsh climate, and a Norwegian-Danish dependency since 1262, was not much coveted by European powers, despite her fertile fishing grounds, technologically accessible since the early 15th Century. In 1518 and 1524, Danish King Christian I unsuccessfully tried to pledge Iceland against a loan from English King Henry VIII. In 1535, King Christian III also tried to do this, but again Henry VIII turned down the request. In 1645, King Christian IV tried to pledge Iceland against a loan from Hanseatic merchants, but yet again, there was not sufficient interest. Indeed, so harsh seemed Iceland’s climate that in 1784–5, after a massive vulcanic eruption and an earthquake, it was seriously contemplated in Copenhagen to evacuate the Icelandic population to other parts of the Danish realm. However, during the Napoleonic Wars the British government briefly considered annexing Iceland. Sir Joseph Banks, who had toured Iceland, wrote three reports, in 1801, 1807 and 1813, recommending this. Ultimately, the British government decided against it: Iceland was not sufficiently attractive. In 1868, a report was written at the initiative of the U.S. Secretary of State William H. Seward on a possible purchase of Iceland, but the idea was so ill-received that Secretary Seward made no further move. The conclusion is that Iceland was a marginal society until it became, in the 20th century, strategically important, enjoying the military and political protection of the U.S. from 1941 to 2006. After that, Iceland became marginal again and thus expendable.